Crystal structure and Hirshfeld surface analysis of 3-({4-[(4-cyanophenoxy)carbonyl]phenoxy}carbonyl)phenyl 4-(benzyloxy)-3-chlorobenzoate - S. Selvanandan; H. Anil kumar; H. T. Srinivasa; B. S. Palakshamurthy (Acta Crystallographica Section E: Crystallographic Communications, 2022)
The title compound, C35H22ClNO7, is a non-liquid crystal with a bent-shaped molecule. The dihedral angles between adjacent aromatic rings in the molecule (starting from the cyanobenzene ring) are 72.61 (2), 87.69 (4), 64.08 (2) and 88.23 (2)°, indicating that adjacent rings are close to perpendicular to each other. In the crystal, the molecules are linked by weak C—H...N and C—H...π interactions, thereby forming a two-dimensional supramolecular architecture in the ac plane. The most important contributions to the crystal packing arise from H...H (59.3%), S...H (27.4%) and O...H (7.5%) interactions, as determined by a Hirshfeld surface analysis.